2018
DOI: 10.1002/ijc.31664
|View full text |Cite
|
Sign up to set email alerts
|

Global cancer incidence in older adults, 2012 and 2035: A population‐based study

Abstract: Population ageing has substantially contributed to the rising number of new cancer cases worldwide. We document cancer incidence patterns in 2012 among older adults globally, and examine the changing magnitude of cancer in this age group over the next decades. Using GLOBOCAN 2012 data, we presented the number and proportion of new cancer cases, and the truncated age-standardised incidence rates among adults aged 65 years and older for all cancer sites combined and for the five most common cancer sites by world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
299
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 481 publications
(322 citation statements)
references
References 40 publications
10
299
3
10
Order By: Relevance
“…a lack of skilled staff, poor access to surgery, poor infrastructure—most sub‐Saharan African countries have no geriatricians, physicians are not sufficiently trained in geriatrics, and geriatric oncology is not developed in sub‐Saharan Africa . The considerable rise in number of older adults with cancer expected in next decades will challenge the acute disease‐centered health systems in sub‐Saharan African countries, which will have to adapt rapidly to address the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a lack of skilled staff, poor access to surgery, poor infrastructure—most sub‐Saharan African countries have no geriatricians, physicians are not sufficiently trained in geriatrics, and geriatric oncology is not developed in sub‐Saharan Africa . The considerable rise in number of older adults with cancer expected in next decades will challenge the acute disease‐centered health systems in sub‐Saharan African countries, which will have to adapt rapidly to address the problem.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, although significant gains in palliative care development have been made in Africa, these services are still not available in most sub-Saharan African countries. 38 Given the expected rise in the number of older patients with cancer in the region, 37 encouraging the development of palliative care is essential through the provision of training to professional staff and better access to palliative medications. 39 Our study represents the most comprehensive picture of the cancer burden in older adults in sub-Saharan Africa, using the high quality incidence data available within the region.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly, life expectancy in most of Europe has increased by about 5% over the past 15 years. Almost 11% of women and 7.5% of men were already 65 years or older in 2016 (https://www.populationpyramid.net/europe/ 2016/); those are the ages where about half of all the cancers in Europe occur (Pilleron et al, 2018).…”
Section: Cancer Burden In Europementioning
confidence: 99%
“…However, few studies have analyzed the impact of SPA on health within a population affected by a disease. Among older people, an important health issue concerns oncology: indeed, it is estimated that by 2035, patients over 65 years of age will represent 60% of newly diagnosed cancers in the world . Therefore, studying SPA (and its effects) in this particular population is of great importance: anticipating older cancer patients with higher risks of more negative outcomes is a major issue and could lead to improve medical effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Among older people, an important health issue concerns oncology: indeed, it is estimated that by 2035, patients over 65 years of age will represent 60% of newly diagnosed cancers in the world. 19 Therefore, studying SPA (and its effects) in this particular population is of great importance: anticipating older cancer patients with higher risks of more negative outcomes is a major issue and could lead to improve medical effectiveness. It is all the more important as we know that SPA is more negative in oncological context: indeed, a recent study among 1140 participants has observed that individuals with cancer have a more negative SPA than people without cancer.…”
Section: Introductionmentioning
confidence: 99%